NUTRITION CARE PROCESS IN PATIENTS BRONCHOPULMONARY DYSPLASIA WITH SEVERE MALNUTRITION - Nadia Rafa; Hiya Alfi Rahmah; Sobir Arbangi (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2023)
Introduction: Patient with malnutrition condition accompanied by infection diseases such as bronchopulmonary have an interacts with each other, so that the nutrition care process was needed to improve condition and sufficient of the nutrition. Nutrition Care Process have four stages, there are assessment, diagnosis, intervention, dan monitoring evaluation. Aim: To implementation of Nutrition Care Process in bronchopneumonia patien with severe malnutrition during three days of intervention.   Materials and Methods: This case study was conducted in November 2022 in hospitalized patients of RSUD Cilacap. NCP were made for 3 consecutive days. Aspects that will be observed are aspect of antrophometry, biochemical, clinical physic, and food intake. Result: After carrying out the nutrition care process for 3 consecutive days, the physical clinic patient began to improve, marked by the condition of the patient who looked fit and medical complications were resolved, biochemical laboratory result such as leukocyte and platelets also showed decrease to normal values, and the patient’s intake increased every day. Conclusion: Based on monitoring and evaluation result that have been carried out, overall intervention given is achived.